1982
DOI: 10.1212/wnl.32.11.1272
|View full text |Cite
|
Sign up to set email alerts
|

Electro‐oculographic findings in Machado‐Joseph disease

Abstract: Electro-oculographic recordings (EOG) were made on 26 patients with Machado-Joseph disease or at genetic risk for that disease. All patients with clinically apparent disease (ataxia, dysarthria, spasticity, or ophthalmoparesis) had abnormal eye movements. Defects in caloric response, sinusoidal tracking, opticokinetic nystagmus (OKN), refixation saccades, and presence of gaze paretic nystagmus were detected in that order of frequency. Fourteen subjects were clinically at risk but had normal neurologic examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

1983
1983
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 0 publications
0
8
1
Order By: Relevance
“…Machado-]oseph's disease (9), spinocerebellar degeneration (31), and Gerstmann-Sträussler-Scheinker disease (11). However, in our patients, the early-onset, lack of progression after childhood, and the absence of any non-oculomotor neurological signs in most of our cases are not compatible with these conditions.…”
Section: Clinical Aspectscontrasting
confidence: 68%
“…Machado-]oseph's disease (9), spinocerebellar degeneration (31), and Gerstmann-Sträussler-Scheinker disease (11). However, in our patients, the early-onset, lack of progression after childhood, and the absence of any non-oculomotor neurological signs in most of our cases are not compatible with these conditions.…”
Section: Clinical Aspectscontrasting
confidence: 68%
“…If saccadic slowing is caused by central oculomotor pathology in the brain stem, the patient shows gaze nystagmus, unless the lesion is confined to a small region or the range of eye movement is severely restricted. For example, neurological examinations of patients with Machado-Joseph disease, a neurodegenerative disease with oculomotor abnormalities that include slow saccades [39] and neuronal loss in the oculomotor nuclei, show a high incidence of gaze-evoked nystagmus [14,30,33,39] (65.1%, according to Shimizu et al [39]). There are several central nervous system diseases that mainly affect saccade velocity, for example Niemann-Pick disease [5,10,34,45], Gaucher's disease [10,43] and progressive supranuclear palsy [12,40].…”
Section: Discussionmentioning
confidence: 99%
“…Neither showed responses in the caloric test, suggesting severe vestibular impairment. Previous studies found that poor or no caloric response was observed in MJD patients relatively frequently [3,5,7], but most of these evaluations done at least several years after initial symptom onset. Our present study clearly showed severe disturbance in the caloric test was the earliest phenomenon in genetically confirmed MJD.…”
Section: Discussionmentioning
confidence: 99%
“…Selective vulnerability is a major feature of MJD. Among neuronal structures, the vestibular system is known to be damaged [3][4][5][6][7], but little is known about precisely when vestibular dysfunction occurs. To find out, we evaluated caloric vestibular response in two patients with genetically confirmed MJD early on after initial symptom onset.…”
Section: Introductionmentioning
confidence: 99%